System Design and Usability Evaluation of Ghana Music Documentation System Using the System Usability Scale - Yussiff, A.-S. (Springer Science and Business Media Deutschland GmbH, 2021)
Ghana lacks proper establishment of primary sources of information on Ghanaian music, musicians, artists, and performance group. In addition, there is lack of a channel for acquiring such data. In an attempt to solve these problems, an online system entitled, Ghana Music Documentation System (GMDS) was developed and evaluated. The research aim at developing and evaluating a sustainable, usable and interactive online database of institutions, musical practices, musicians, artists, cultural entrepreneurs, performance groups, producers, as well as other stakeholders in the fields of music performance, education, production, promotion, and dissemination. In addition, the GMDS will allow users to browse, search for musical information and mapped Ghanaian music information for further analysis and visualization. In order to achieve these objectives, the development we followed five development approach: background study, identification of need and establishing requirements, designs, building an interactive system, and evaluation. We employed the System Usability Scale (SUS) instrument to evaluate the usability of GMDS and the result shows that the GMDS has an average SUS score of 81.6. This demonstrated that the GMDS system is acceptable, has a grade scale of B and the rating adjective is excellent. Based on the evaluation result, we concluded that the system proposes an innovative mapping technique, and will serve as a powerful primary repository for mapping Ghanaian music thereby becoming a reliable, effective and efficient research tool for all. Â© 2021, Springer Nature Switzerland AG.